Assessment of Phenotypic Diversity among Ethiopian Coriander Accessions (Coriandrum sativum) at Kulumsa, Southeastern Ethiopia - Wegayehu Tilahun, Gizaw; Fikire, Demis; Tsagaye, Dasta; Gebretensay, Fekadu (International Journal of Bio-resource and Stress Management, 2023)
A phenotypic diversity study was carried out under field conditions in the meher season ((July–November 2019 and 2020) at Kulumsa, Southeast Ethiopia to assess variables that directly affect seed yield, contribute to the total phenotypic variance, and classify coriander accessions. Twenty-five Ethiopian coriander accessions were laid out in a simple lattice design with two replications. Eight morphological parameters of the coriander accessions showed highly significant differences (p≤0.01)) in the combined analysis of variance. Plant height, the number of umbellets umbel-1, the number of seeds umbel-1, and the seed yield plant-1 all had a positive and direct effect on the seed yield (t ha-1). The first two principal components contributed 62.6% of the total phenotypic variation. Number of umbels plant-1, number of umbellets umbel-1, seed yield plant-1, and seed yield (t ha-1) were the characteristics with the highest loading effects in the first principle component, and plant height and seed yield (ha-1) in the second. Six clusters of accessions were created. About 28% and 8% of the studied accessions were found in the largest cluster (I) and clusters (V and VI), respectively. The highest inter-cluster distances were observed between VI and III (D2 = 159.21), IV and III (D2 = 155.84), and VI and I (D2 = 113.26) clusters. Crossing between accessions included in those clusters could produce highly heterotic responses and segregants. In general, this study demonstrated significant phenotypic diversity among the tested accessions and could be used in improvement programs to develop desirable coriander cultivars.